Dynamic Subcellular Localization of Iron during Embryo Development in Brassicaceae Seeds - Ibeas, Miguel A.; Grant-Grant, Susana; Navarro, Nathalia; Perez, M. F.; Roschzttardtz, Hannetz (Frontiers in Plant Science, 2017)
Iron is an essential micronutrient for plants. Little is know about how iron is loaded in embryo during seed development. In this article we used Perls/DAB staining in order to reveal iron localization at the cellular and subcellular levels in different Brassicaceae seed species. In dry seeds of Brassica napus, Nasturtium officinale, Lepidium sativum, Camelina sativa and Brassica oleracea iron localizes in vacuoles of cells surrounding provasculature in cotyledons and hypocotyl. Using B. napus and N. officinale as model plants we determined where iron localizes during seed development. Our results indicate that iron is not detectable by Perls/DAB staining in heart stage embryo cells. Interestingly, at torpedo development stage iron localizes in nuclei of different cells type, including integument, free cell endosperm and almost all embryo cells. Later, iron is detected in cytoplasmic structures in different embryo cell types. Our results indicate that iron accumulates in nuclei in specific stages of embryo maturation before to be localized in vacuoles of cells surrounding provasculature in mature seeds.